Outsourcing and flexible accumulation of capital notes on the critical-theoretical organic changes of capitalist production - Alves, Giovanni (2011)
This essay seeks to provide theoretical and critical elements to see the outsourcing process as a compositional feature of the new configuration of flexible capitalism in the context of globalization of capital. Outsourcing is designed to rationalize, under the new conditions of competition and accumulation, the exploitation of the workforce employed within the new capitalist mode of cooperation: cooperation complex, higher stage of the great industry under the terms of the information revolution.